1989
DOI: 10.1063/1.1140324
|View full text |Cite
|
Sign up to set email alerts
|

20-ps timing resolution with single-photon avalanche diodes

Abstract: Articles you may be interested inCustom single-photon avalanche diode with integrated front-end for parallel photon timing applications Rev. Sci. Instrum. 83, 033104 (2012); 10.1063/1.3692737Actively quenched singlephoton avalanche diode for high repetition rate timegated photon counting Rev. Sci. Instrum. 67, 55 (1996); 10.1063/1.1146551Photoluminescence lifetime microscope spectrometer based on timecorrelated singlephoton counting with an avalanche diode detector Rev.Performance comparison of a singlephoton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(63 citation statements)
references
References 19 publications
0
63
0
Order By: Relevance
“…SPAD detectors so far reported can be divided in two groups, according to the depletion layer of the p-n junction, which can be thin, typically 1 m [11,12], or thick, from 20 m to 150 m [7][8][9][13][14][15]. The main features of thin-junction SPADs are: breakdown voltage V B of 20-50 V; small active area, with diameter from 20 m to 100 m; fairly good quantum efficiency in the visible range, about 45% at 500 nm and declines to 32% at 630 nm and to 15% at 730 nm, and is still useful in the NIR, being about 10% at 830 nm and a few 0.1% at 1064 nm.…”
Section: Single-photon Detectionmentioning
confidence: 99%
“…SPAD detectors so far reported can be divided in two groups, according to the depletion layer of the p-n junction, which can be thin, typically 1 m [11,12], or thick, from 20 m to 150 m [7][8][9][13][14][15]. The main features of thin-junction SPADs are: breakdown voltage V B of 20-50 V; small active area, with diameter from 20 m to 100 m; fairly good quantum efficiency in the visible range, about 45% at 500 nm and declines to 32% at 630 nm and to 15% at 730 nm, and is still useful in the NIR, being about 10% at 830 nm and a few 0.1% at 1064 nm.…”
Section: Single-photon Detectionmentioning
confidence: 99%
“…This laser emitted pulses at the 850-nm wavelength of between 10-and 20-ps duration and of pulse energy 7-10 pJ. The clean temporal pulse shape of these lasers complemented the use of the activelyquenched shallow junction Si SPAD detectors [10]- [12]. Such detectors are capable of 20-ps resolution timing at count rates in excess of 10 6 per second.…”
Section: Short-range Time-of-flight Photon-counting Systemmentioning
confidence: 99%
“…Here it was found that a wide range of beam splitting ratios can be readily achieved, so that the constraints derived above can be readily satisfied. Concerning the detectors required for this protocol, we note that fast photodetectors with timing jitter on the order of tens of picoseconds are now a well established technology [45]. In the current protocol, repeated detections are not required (each detector only needs to fire once to implement photon subtraction, for instance) so detector dead-time plays no role in limiting the clock speed for the protocol.…”
Section: Discussionmentioning
confidence: 99%